Environmental Dimensions of the Agrarian Transition in the Uplands of the Lao PDR - Lestrelin, Guillaume; Castella, J.C. (2010)
The agrarian transition is considered as one of the most important drivers of socioeconomic transformation that has occurred over the past three centuries. While abundant, the related scientific literature exhibits significant lacunae with regard to the links between social change, ecological dynamics and environmental politics. Intended as a contribution to a better understanding and theorization of the agrarian transition, this project combines physical measurements, aimed at characterizing the state and dynamics of the ecological milieu, with surveys on local livelihood change, environmental knowledge, discourses and practices in contrasted localities of the Laotian uplands. On these grounds, a comparative analysis of local trajectories of agrarian transition is undertaken.